ANALYSIS OF EMPLOYER BRAND AND EMPLOYEE RETENTION RELATION WITH EMPLOYEE ENGAGEMENT AND JOB SATISFACTION AS MEDIATION VARIABLES: A STUDY ON AN INDONESIAN PETROCHEMICAL COMPANY - Prasetiowati Prasetiowati (Green Publisher, 2023)
Managing employee retention rates is a challenge for a company where a high retention rate will optimize the effectiveness and efficiency of the company by maintaining highly qualified employees in the company. This study aims is to analyze the relationship between employer brand and employee retention by proposing two mediating variables, namely employee engagement and job satisfaction. This study aims to analyze the relationship between employer brand and employee retention by proposing two mediating variables, namely employee engagement and job satisfaction. The research is a quantitative research that uses SEM (structural equation modeling) as an analytical method. The data were tested empirically and in the form of descriptive statistics on 173 respondents who were employees of the company. The results of the study are expected to indicate a positive relationship between employer brand and employee retention, either directly or indirectly through employee engagement and job satisfaction as mediating variables